A Analysis of PTSL Implementation in Supporting Agrarian Reform in Indonesia: National Literature Approach - Aziz, Abdul; Azhar, Azhar (PERSPEKTIF, 2025)
Agrarian reform in Indonesia faces complex challenges in the implementation of land registration. This study analyzed 43 national scientific publications related to Complete Systematic Land Registration (PTSL) to understand the dynamics of land policy implementation. Using the literature study method with the theoretical approach of Van Meter and Van Horn, the study explores the factors that influence the success of land registration programs in Indonesia. The results show that PTSL has registered 118,047,564 land plots (93.69% of the national target), with significant achievements but facing challenges, including limited resources, geographical constraints, and variations in implementation between regions. Key success factors include inter-organizational communication, local government support, and community participation. The research recommends improved institutional coordination, resource capacity building, and more comprehensive socialization strategies. The study's findings provide a new conceptual framework for understanding land policy implementation in Indonesia and an empirical basis for developing more effective and equitable agrarian reform.